VIEWS OF EASTERN SCIENTISTS AND FAMOUS TEACHERS ON ENVIRONMENTAL EDUCATION OF CHILDREN - Tilavova Nargiza Turabovna (American Journals, 2024)
Environmental education and education it is important to use the scientific heritage of Eastern thinkers in the formation of concepts about culture. Because our great thinkers have never bypassed the question of the relationship of Man and nature in their works. In their works, environmental education is expressed not only in the way of nature conservation, but in connection with such important problems as humanity, the development of human thought, the education of spiritual and moral qualities.
Keywords: Environmental education, environmental knowledge, biological characteristics of plants and animals, thinkers, ecological culture, explanation, teaching